The Relationship Between Curriculum Innovation, Lecturer Interaction Quality, and Digital Learning Styles on the Effectiveness of Islamic Education Among Millennials - Asnawan Asnawan; Citra Dewi; Ali Nasith; Anuwat Sohwang (Nadwa: Jurnal Pendidikan Islam, 2025)
The rapid digital transformation in education has posed unique challenges and opportunities for Islamic education, particularly in meeting the learning needs of the millennial generation. This study investigates the influence of curriculum innovation, lecturer interaction quality, and digital learning styles on the effectiveness of Islamic education among millennials in higher education institutions. Utilizing a quantitative, causal-associative approach, data were collected through structured questionnaires from students and lecturers. The analysis used Structural Equation Modeling–Partial Least Squares (SEM-PLS) via SmartPLS 4.0. The results revealed that curriculum innovation and lecturer interaction have a strong, positive, and significant effect on educational effectiveness, while digital learning demonstrates a weaker but statistically significant effect. The study also confirms that millennial characteristics moderate these relationships, particularly enhancing the effects of curriculum innovation and digital learning. These findings suggest that to improve the effectiveness of Islamic education in the digital era; institutions should prioritize integrated strategies that combine innovative curriculum design, interactive pedagogical methods, and digitally adaptive learning environments aligned with generational learning preferences. This research contributes to the literature by offering a holistic and empirical framework that links educational Innovation with generational dynamics in Islamic higher education.